2016
DOI: 10.1007/s10100-016-0441-z
|View full text |Cite
|
Sign up to set email alerts
|

Synchronizing vans and cargo bikes in a city distribution network

Abstract: One of the significant side-effects of growing urbanization is the constantly increasing amount of freight transportation in cities. This is mainly performed by conventional vans and trucks and causes a variety of problems such as road congestion, noise nuisance and pollution. Yet delivering goods to residents is a necessity. Sustainable concepts of city distribution networks are one way of mitigating difficulties of freight services. In this paper we develop a two-echelon city distribution scheme with tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(48 citation statements)
references
References 21 publications
0
48
0
Order By: Relevance
“…Anderluh [22] evaluated a two-echelon city distribution scheme with temporal and spatial synchronization between cargo bikes and vans based on a greedy randomized adaptative search procedure with path relinking. Authors concluded that costs and emissions can be saved by the combined usage of cargo bikes and vans instead of vans alone.…”
Section: State Of the Artmentioning
confidence: 99%
“…Anderluh [22] evaluated a two-echelon city distribution scheme with temporal and spatial synchronization between cargo bikes and vans based on a greedy randomized adaptative search procedure with path relinking. Authors concluded that costs and emissions can be saved by the combined usage of cargo bikes and vans instead of vans alone.…”
Section: State Of the Artmentioning
confidence: 99%
“…Finally, input parameters e.g., cost values or locations, can be changed, and the sensitivity of these changes can be incorporated in the analysis. Simulation has successfully been used before in urban logistics [35][36][37][38][39].…”
Section: Simulationmentioning
confidence: 99%
“…Starting from the concept of green city, Huang et al [9] analyzed the factors that restrict the green development of urban distribution, and put forward a new urban distribution model. Alexandra et al [10] innovatively proposed a two-level urban distribution model based on time and space synchronization, and constructed a corresponding distribution path optimization model.…”
Section: Introductionmentioning
confidence: 99%
“…Suppose N = 10, K = 3, the encoding dimension is (10 + 3 − 1) × 1 = 12 × 1, thus a possible encoding can be (0.12, 0.37, 0.22, 0.96, 0.56, 0.35, 0.76, 0.57, 0.38, 0.91, 0.71, 0.26). Using the random key decoding rule, it is easy to get the integer arrangement (1,5,2,12,7,4,10,8,6,11,9,3). The integers 11 and 12 are the so-called sub-path segmentation, and the vehicle routes are:…”
mentioning
confidence: 99%